Efektivitas Paparan Medan Magnet Lemah Terhadap Tingkat Kesempurnaan Pembakaran Bahan Bakar Minyak Beroktan Rendah: Shinta Monika Utami, Giner Maslebu, dan Nur Aji Wibowo - Shinta Monika Utami Shinta Monika Utami; Giner Maslebu Giner Maslebu; Nur Aji Wibowo Nur Aji Wibowo (Jurnal Fisika dan Aplikasinya, 2019)
Increasing levels of octane fuel in order to efficient its increasingly scarce use has been done. However, consumers still maintain the use of low-octane fuel because of its affordable price. The treatment in the form of magnetic field exposure on fuel is a means that is believed able to improve the completeness of combustion. In this study, tests were conducted on low-octane fuel with exposure to weak magnetic fields aimed at streamlining the scarcity of low-octane fuel usage. Exposure to weak magnetic fields in the storage tank before going into the combustion process will stretch the hydrocarbon bonds so that the hydrocarbon molecules are easier to oxidise. Fuel exposed to a weak magnetic field is applied to a two-stroke engine with varying engine workloads. The level of combustion completeness is measured from reduction of fuel consumption and the percentage of O2 emissions. The results of this study indicate that exposure to weak magnetic fields on low-octane fuel significantly improves the completeness of combustion processes.